DEVELOPING ENGLISH SPEAKING THROUGH OME TV - Yusuf, Emi Marlina M; Talib, Ahmad; Tahir, Muh. (Universitas Negeri Makassar, 2024)
The objective of this research was to find out this study to determine whether using Ome TV could develop students' speaking skills. This research adapted a pre-experimental design. This research took place at SMAN 3 Makassar. The population of this research was the eleventh-grade students of SMAN 3 Makassar in the academic year 2022-2023. The XI IPA 2 class was selected to be the sample of this research. The research utilized a speaking test administered both as a pretest and a posttest. The results indicated that using Ome TV to develop English-speaking skills was effective. This is evidenced by the mean score of 7.49 on the pretest and 10.9 on the posttest, showing an increase of 45.4% in students' scores.